1993
DOI: 10.1172/jci116687
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the donor splice site of intron 4 in the glucokinase gene causes maturity-onset diabetes of the young.

Abstract: Missense and nonsense mutations in the glucokinase gene have recently been shown to result in maturity-onset diabetes of the young (MODY), a subtype of non-insulin-dependent diabetes mellitus with early age of onset. Glucokinase catalyzes the formation of glucose-6-phosphate and is involved in the regulation of insulin secretion and integration of hepatic intermediary metabolism. Nucleotide sequence analysis of exon 4 and its flanking intronic regions of the glucokinase gene, in four hyperglycemic individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Overwhelming evidence indicates that glucokinase is the primary component of the ␤-cell glucose-sensor apparatus and accounts for the characteristic glucose concentration dependence of insulin secretion (27,42,52). This is supported by the fact that genetic mutations in glucokinase can cause a form of type II diabetes mellitus designated maturity-onset diabetes of the young (MODY) and that catalytic activities of mutant glucokinases encoded by MODY genes are reduced (53)(54)(55). MODY is an autosomal dominant disorder and occurs despite the presence of one normal glucokinase allele (53).…”
Section: Discussionmentioning
confidence: 99%
“…Overwhelming evidence indicates that glucokinase is the primary component of the ␤-cell glucose-sensor apparatus and accounts for the characteristic glucose concentration dependence of insulin secretion (27,42,52). This is supported by the fact that genetic mutations in glucokinase can cause a form of type II diabetes mellitus designated maturity-onset diabetes of the young (MODY) and that catalytic activities of mutant glucokinases encoded by MODY genes are reduced (53)(54)(55). MODY is an autosomal dominant disorder and occurs despite the presence of one normal glucokinase allele (53).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic investigations in families with strong diabetes aggregation have demonstrated that mutations in the coding regions of the glucokinase gene (GCK) on chromosome 7 result in a familial subtype of NIDDM, characterized by an early age of onset and autosomal dominant inheritance with high penetrance (maturity onset diabetes of young 2 [MODY 2]) (1)(2)(3)(4)(5)(6). Glucokinase phosphorylates glucose to glucose-6-phosphate and plays a major role in the regulation and integration of glucose metabolism in pancreatic ␤ cells and hepatocytes (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…All GCK mutations associated with hyperglycemia that have so far been identified have been localized to exons that are common to both the pancreatic and hepatic isoforms of the enzyme (1)(2)(3)(4)(5)(6). It is therefore certain that the hepatocytes also express the mutant enzyme, although the consequences of these mutations on the hepatic metabolism of glucose, and their role in the pathogenesis of hyperglycemia remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported an assay that used the presence of ectopic transcripts within lymphoblastoid cells to examine the effect of three splice site mutations of the HNF-1α gene [18]. This approach has also been used to examine the effects of a splice site mutation in the glucokinase (GCK) gene [19].…”
Section: Introductionmentioning
confidence: 99%